Influence of tool traverse speed on microstructure and mechanical properties of CuNi/B4C surface composites. (2nd January 2021) - Suganya Priyadharshini, G.; Satish Kumar, T.; Anbuchezhian, N.; Vaira Vignesh, R.; Subramanian, R.; Velmurugan, T.; Kamal Basha, K.
ABSTRACT: The study presents an analysis specifically on the effect of tool traverse speed (one of the most influential process parameters of friction stir processing) on the microstructural evolution, microhardness, tensile behaviour, and tribological characteristics of CuNi/B4 C surface composite. The friction stir processing trials were performed at the following tool traverse speeds: 20, 25, 30, 35, and 40 mm min −1 . The microstructural analysis confirmed the homogeneous dispersion/agglomeration of B4 C particles in the specimens that are friction stir processed at low/high traverse speed. The results indicate that friction stir processing of specimens beyond tool traverse speed of 30 mm min −1 results in undesirable microhardness, tensile strength, and wear resistance. A comprehensive correlation of microstructural evolution with the mechanical properties, fracture mechanism, and tribological characteristics of the fabricated surface composites is presented.